2016
DOI: 10.1536/ihj.16-007
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan Reduces Long-Term Total Medical Expenses and Length of Stay in Aquaporin-Defined Responders

Abstract: SummaryThe vasopressin type-2 antagonist tolvaptan (TLV) has clinical advantages including amelioration of congestion and normalization of hyponatremia in patients with decompensated heart failure (HF). However, there have been no studies on the cost-effectiveness of TLV therapy. We enrolled 60 consecutive hospitalized patients with stage D HF who received TLV [TLV (+) group], and 60 propensity score-matched HF patients without TLV treatment [TLV (-) group]. We excluded 54 patients who died or received cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…3) [27]. As a result, tolvaptan therapy reduced the total medical expense in the responders but not in the non-responders [29]. A prospective study of long-term tolvaptan therapy in predicted responders is ongoing [30].…”
Section: Respondermentioning
confidence: 99%
“…3) [27]. As a result, tolvaptan therapy reduced the total medical expense in the responders but not in the non-responders [29]. A prospective study of long-term tolvaptan therapy in predicted responders is ongoing [30].…”
Section: Respondermentioning
confidence: 99%
“…The propensity score was estimated using a multivariate logistic regression analysis including tolvaptan therapy as the dependent variable, and the following 15 explanatory variables as covariates: Child-Pugh classification, HCC and its stage at the start of the observation period, background liver status, presence or absence of diabetes, total bilirubin level, alanine aminotransferase level, red blood cell count, platelet count, prothrombin time (%), and Creactive protein level, in addition to the variables used in previous studies, 4,25 including age, sex, serum sodium concentration, and serum creatinine concentration. Then, oneto-one matching with a 0.01 caliper was carried out to create matched patient pairs.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A Japanese study showed tolvaptan reduced the cost of treatment for heart failure in aquaporin-defined responders. 33) Compared with conventional therapy, tolvaptan showed lower medical cost (1,120,000 yen/year versus 3,120,000 yen/year, respectively) and shorter hospital stay (30 days versus 70 days, respectively). Tolvaptan could be cost-effective in certain types of heart failure.…”
Section: Specific Cost-effectiveness Analysis In the Field Of Cardiologymentioning
confidence: 90%